Behavioral Responses of Invasive and Nuisance Vertebrates to Harvesting: A Mechanistic Framework - Diquelou, Marie C.; Griffin, Andrea S. (Frontiers in Ecology and Evolution, 2020)
Wildlife species are harvested for a variety of purposes. This is known to drive phenotypic change, particularly in the context of exploitative harvesting. As the impact of invasive alien species grows, and new conflicts with nuisance species arise, management of these problematic species has emerged as a key topic. Yet there is little to no attention directed to whether and how species are changing as a consequence of lethal control, particularly in terms of their behavior. In this synthesis, we draw attention to the fact that nuisance and invasive species undergoing control are likely to exhibit behavioral change. First, we highlight the potential consequences of behavioral responses to control on species’ management and ecological impact. Second, we provide a framework of mechanisms that can lead to behavioral responses to lethal control. Three categories are described: evolutionary mechanisms, cognitive mechanisms and stress mechanisms. Understanding which mechanism underlies a behavioral response is paramount as it allows to predict how prevalent the response will be in the population. We argue for increased monitoring of behavior by managers and more research efforts into the mechanisms of behavioral responses to novel threats in order to better predict and mitigate unforeseen and unwanted behavioral change.